The Interplay between PP2A and microRNAs in Leukemia - Ruvolo, Peter P. (Frontiers in Oncology, 2015)
Protein Phosphatase 2A (PP2A) is a serine/threonine phosphatase family whose members have been implicated in tumor suppression in many cancer models. In many cancers, loss of PP2A activity has been associated with tumorigenesis and drug resistance. Loss of PP2A results in failure to turn off survival signaling cascades that drive drug resistance such as those regulated by Protein Kinase B (AKT). PP2A is responsible for modulating function and controlling expression of tumor suppressors such as p53 and oncogenes such as BCL2 and MYC. Thus PP2A has diverse functions regulating cell survival. The importance of microRNAs (miRs) is emerging in cancer biology. A role for miR regulation of PP2A is not well understood however recent studies suggest a number of clinically significant miRs such as miR-155 and miR-19 may include PP2A targets. We have recently found that a PP2A B subunit (B55a) can regulate a number of miRs in acute myeloid leukemia (AML) cells. The identification of a miR/PP2A axis represents a novel regulatory pathway in cellular homeostasis. The ability of miRs to suppress specific PP2A targets and for PP2A to control such miRs can add an extra level of control in signaling that could be used as a rheostat for many signaling cascades that maintain cellular homeostasis. As such, loss of PP2A or expression of miRs relevant for PP2A function could promote tumorigenesis or at least result in drug resisatnce. In this review, we will cover the current state of miR regulation of PP2A with a focus on leukemia. We will also briefly discuss what si known of PP2A regulation of miR expression.